Effects of injection pressure on ignition and combustion characteristics of diesel in a premixed methanol/air mixture atmosphere in a constant volume combustion chamber. (15th October 2017) - Yao, Chunde; Hu, Jiangtao; Geng, Peilin; Shi, Junjie; Zhang, Defu; Ju, Yusheng
Highlights: The combustion characteristics of diesel in MAA at different injection pressures were investigated. The inhibitory effect of methanol on diesel ignition was enhanced at high injection pressure. Due to the addition of methanol, the peak values of AHRR were higher and the combustion durations became shorter. The differences of FLoL between in AA and MAA became smaller with the combustion continuing. The values of SINL and TINL were both lower in MAA than those in AA. Abstract: The experiments on the ignition and combustion characteristics of diesel in air atmosphere (AA) and premixed methanol/air mixture atmosphere (MAA) were conducted in a constant volume combustion chamber (CVCC) equipped with a high pressure common-rail injection system. The ignition and combustion processes were recorded by a high-speed camera and a combustion pressure acquisition system. Results show that with the increase of injection pressure from 40 to 160 MPa, the flame lift-off length (FLoL) becomes longer; and the ignition delay is shortened from 2.80 ms to 2.03 ms (AA) and 2.90 ms to 2.27 ms (MAA) respectively; and correspondingly the combustion duration is shortened from 5.17 ms to 2.47 ms (AA) and 4.83 ms to 2.13 ms (MAA). Compared those in AA, the ignition delay is prolonged by 0.14 ms on average, while the combustion duration is shortened by 0.27 ms in MAA. At high injection pressure, the moments that the maximum combustion pressure occurs and the apparent heat release rates (AHRR) starts to rise are advanced; while in MAA both of them are delayed; and the peak value of AHRR increases. With the increase of injection pressure, both spatially integrated natural luminosity (SINL) and time integrated natural luminosity (TINL) reduce significantly, but the reduction trends of TINL weaken. Due to the addition of methanol, the FLoL of diesel becomes longer, and the SINL and TINL in MAA are both lower than those in AA.